CSR DAN GOOD GOVERNANCE: KATALISATOR HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Muttaqiin, Ninnasi; Bilqis, Emilda (Ecopreneur.12, 2025)
Stock price fluctuations in the mining sector are influenced by multiple factors, among which the implementation of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) plays a strategic role. This research aims to examine the impact of these two elements on the stock prices of mining companies listed on the Indonesia Stock Exchange. Employing a quantitative approach, the research used secondary data from 27 selected companies, drawn purposively from a total population of 64 companies over the 2019–2022 period. The data were analyzed using multiple linear regression. The findings reveal that CSR and GCG, when assessed simultaneously, have a significant effect on stock prices. However, individually, CSR measured by its disclosure index does not significantly influence stock price movements. Conversely, GCG components represented by the board of commissioners and independent commissioners show a significant positive impact. Other elements of GCG, such as the audit committee, managerial ownership, and institutional ownership, do not demonstrate a significant relationship with stock price. These results suggest that strong corporate governance is more closely monitored and valued by the market compared to CSR activities in the context of mining companies in Indonesia.